The Impact of Growth in Tourism on Economic and Human Development – Incorporating a Systematic Literature Review - THAO, Hoang Thi Phuong; BAKUCZ, Márta (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022, 2022)
This article is purposed to address the vital research aims: (1) to examine the impact of the growth in tourism on economic and human development; (2) to understand the current state of research between three observed variables in the development process; (3) to find out the  research gap in population , that is the bulk of research concentrate to “tourism led growth hypothesis” but less of “relationship between tourism, economic and human development” in the same study. This research is a systematic literature review using a search-strategy-developing that is based on the PICOC concept. The data collection follows the Prisma diagram sequence. The main keywords are “economic growth”, “tourism development”, “human development” in the 1975 - 2021 period, the 90 articles with at least one citation for the review are collected to clarify the research aims. Some main results are highlighted : ( 1 ) A short-term, long-term, and causal relationship between observed variables of tourism in developing countries, developed countries, and emerging countries. ( 2 ) A set of quantitative research methods in time series was used for analysis. ( 3 ) propose some future research directions. The former results contributed to the identification of the role of tourism in economic development, thereby building a strategy for exploiting and developing sustainable tourism. The latter is to measure the level of human development (in a positive view) through economic development and tourism. Furthermore, it is also to complete a comprehensive economic development strategy on human welfare, quality of life, and sustainability.